2016
DOI: 10.1016/j.clinthera.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Monitoring for the Effective Management of Antihypertensive Drug Treatment

Abstract: In view of a deficiency in the literature on the role of ABPM in assess the efficacy of drug treatment, we put forward proposals to correct this deficiency and guide the prescribing physician on the most appropriate drug administration and dosage over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…For higher risk patients, it has been suggested that repeat ABPM within 2‐3 weeks of treatment initiation would provide useful information on whether adequate reductions in BP have been achieved. Then, if adjustments to therapy are required, ABPM could be repeated every 2‐3 weeks until stable BP control is documented . After control of both daytime and nighttime ambulatory BP has been achieved, ABPM may only be required every 6‐12 months to confirm maintenance of target BP.…”
Section: Resultsmentioning
confidence: 99%
“…For higher risk patients, it has been suggested that repeat ABPM within 2‐3 weeks of treatment initiation would provide useful information on whether adequate reductions in BP have been achieved. Then, if adjustments to therapy are required, ABPM could be repeated every 2‐3 weeks until stable BP control is documented . After control of both daytime and nighttime ambulatory BP has been achieved, ABPM may only be required every 6‐12 months to confirm maintenance of target BP.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, only 12% of patients achieved target BP with office BP compared with more than one third of patients with ABPM. Furthermore, 38% of patients had a change in their medication as a result of ABPM, 32% had a new medication started, and 14% of untreated patients with elevated office BP, who were candidates for drug treatment, were not started on medication because ABPM values were normal . In one Spanish database, 700 000 elderly individuals would have been spared medication if ABPM, instead of office BP, had been performed .…”
Section: Abpm To Determine Efficacy Of Treatmentmentioning
confidence: 99%
“…Furthermore, 38% of patients had a change in their medication as a result of ABPM, 32% had a new medication started, and 14% of untreated patients with elevated office BP, who were candidates for drug treatment, were not started on medication because ABPM values were normal. 14,15 In one Spanish database, 700 000 elderly individuals would have been spared medication if ABPM, instead of office BP, had been performed. 5 On the other hand, the percentage of patients considered eligible for treatment increased by 6% with ABPM, which amounted to 350 000 elderly patients.…”
Section: Ab Pm To De Termine Effic Ac Y Of Tre Atmentmentioning
confidence: 99%
“…This study showed that ABPM identified the patients for whom medication was needed and resulted in an overall reduction in the number of patients treated for hypertension. The conclusion was that ABPM can save money and that the extra costs of providing the technique were more than offset by cost savings from better targeted treatment …”
Section: Abpm To Determine Efficacy Of Treatmentmentioning
confidence: 99%